PENGETAHUAN IBU HAMIL TENTANG BAHAYA MEROKOK TERHADAP KEHAMILAN DAN JANIN - Manurung, Melva (Universitas Prima Indonesia, 2020)
Smoking during pregnancy can endanger pregnancy and the fetus, especially the health of pregnant women and fetal development in the womb. One of the complications of pregnancy that causes fetal death is due to oxygenation disorders. In Indonesia, more than half of households have at least one smoker, and almost all smokers’ smokes at home. The cause of neonatal death is fetal death in utero, asphyxia or respiratory problems due to smoking and premature. This study aims to determine the knowledge of pregnant women about the dangers of smoking to pregnancy and the fetus in Gasaribu Village, Laguboti, Toba Samosir Regency. This research was conducted in September-October 2019 using adescriptive research design. The number of samples was in this study were 40 pregnant women. Sampling is done by using saturated sampling. The results showed that good knowledge of 16 people (40%) was enough 22 people (55%) and less 2 people (5%). The results of this study are expected to be used as additional material in adding knowledge and information to increase real health education (real) to the public about the dangers of smoking to pregnancy and the fetus.